DAMPAK PERTUMBUHAN EKONOMI KOTA SEMARANG TERHADAP KEMACETAN LALULINTAS DI WILAYAH PINGGIRAN DAN KEBIJAKAN YANG DITEMPUHNYA - Soesilowati, Etty (Semarang State University, 2008)
The aim of this research is to know how much is the impact of Semarang economics growth to theintensity of traffic jam on Semarang Ã¢â¬â Mranggen road, and, what is the strategy to solve it. This researchused descriptive percentase and SWOT analysis. The economics growth which is measured is GrossDomestic Product per capita (PDRB) during 1996 Ã¢â¬â 2005, and it had become a free variable. Meanwhile,the level of the annual average traffic jam during 1996 Ã¢â¬â 2005 had become a bounded variable. To knowthe policy strategy, it was done by interviewing some stake holders that has an authority in the field oftransportation. The result of this research showed that the economics growth of Semarang city hadimpact on individual role to the traffic jam as sum of 80,9%. The rest, 44,6% was influenced by someother things such as the activity of micro trader (PKL), parking man, public transportation and also peoplewho crossed the road. Based on SWOT analysis, the most appropriate strategy to solve the traffic jam isby integrated horizontal strategy. It means, all institutions that subordinated by Local Government(Pemda) such as Bapeda, Dinas Perhubungan dan Satpol PP, should work together to overcome thetraffic jam based on each authority. Nevertheless, the role of the police of Demak County as a verticalinstitution is not less important. In the long run, it is important to develop a modern public transportationsystem which is integrated, comfortable and also efficient, geometry road system that will be able toavoid the traffic intersection, and also to educate people how to do a good manner in trafficKeywords: Economic Growth, Traffic Jam, Policy Strategic.